Toxicological Effects of Microplastics and Sulfadiazine on the Microalgae Chlamydomonas reinhardtii - Li, Ze; Dong, Sheng; Huang, Fei; Lin, Langli; Hu, Zhangli; Zheng, Yihong (Frontiers in Microbiology, 2022)
Despite the fact that microplastics (MPs) facilitate the adsorption of environmental organic pollutants and influence their toxicity for organisms, more research is needed on the combination of MPs and antibiotics pollutant effects. In this study, polystyrene MPs (1 and 5 μm) and sulfadiazine (SDZ) were examined separately and in combination on freshwater microalga, Chlamydomonas reinhardtii. The results suggest that both MPs and SDZ alone and in combination inhibited the growth of microalgae with increasing concentration of MPs and SDZ (5 - 200 mg L-1), however, the inhibition rate was reduced by combination. Upon exposure for seven days, both MPs and SDZ inhibited algal growth, reduced chlorophyll content, and enhanced superoxide dismutase (SOD) activities, whereas glutathione peroxidase (GSH-Px) activity was elevated only with the exposure of 1 μm MPs. Fluorescence microscopy and scanning electron microscopy also indicated that particle size contributed to the combined toxicity by aggregating MPs with periphery pollutants. Further, the amount of extracellular secretory protein increased in the presence of MPs, and SDZ removal ratio decreased when MPs and SDZ coexisted, suggesting that MPs affected SDZ metabolism by microalgae. The particle size of microplastics affected the toxicity of MPs on microalgae, and the combined effect of the MPs and the SDZ could be mitigated by MPs adsorption. These findings provide insight into microalgae responses to the combination of MPs and antibiotics in water ecosystems.